Maternal supplementation alone with Lactobacillus rhamnosus HN001 during pregnancy and breastfeeding does not reduce infant eczema. Issue 3 (6th April 2018) - Wickens, Kristin; Barthow, Christine; Mitchell, Edwin A.; Stanley, Thorsten V.; Purdie, Gordon; Rowden, Judy; Kang, Janice; Hood, Fiona; van den Elsen, Lieke; Forbes‐Blom, Elizabeth; Franklin, Isobel; Barnes, Phillipa; et al.
Abstract: Background: In a randomized placebo‐controlled trial, we previously found that the probiotic Lactobacillus rhamnosus HN001 (HN001) taken by mothers from 35 weeks of gestation until 6 months post‐partum if breastfeeding and their child from birth to age 2 years halved the risk of eczema during the first 2 years of life. We aimed to test whether maternal supplementation alone is sufficient to reduce eczema and compare this to our previous study when both the mother and their child were supplemented. Methods: In this 2‐centre, parallel double‐blind, randomized placebo‐controlled trial, the same probiotic as in our previous study (HN001, 6 × 10 9 colony‐forming units) was taken daily by mothers from 14‐16 weeks of gestation till 6 months post‐partum if breastfeeding, but was not given directly to the child. Women were recruited from the same study population as the first study, where they or their partner had a history of treated asthma, eczema or hay fever. Results: Women were randomized to HN001 (N = 212) or placebo (N = 211). Maternal‐only HN001 supplementation did not significantly reduce the prevalence of eczema, SCORAD ≥ 10, wheeze or atopic sensitization in the infant by 12 months. This contrasts with the mother and child intervention study, where HN001 was associated with reductions in eczema (hazard ratio (HR): 0.39, 95% CI 0.19‐0.79, P = .009) and SCORAD (HR = 0.61, 95% 0.37‐1.02). However, differences in the HN001 effect between studies were not significant. HN001 could not be detected in breastmilk from supplemented mothers, and breastmilk TGF‐β/IgA profiles were unchanged. Conclusion: Maternal probiotic supplementation without infant supplementation may not be effective for preventing infant eczema.